Enhancing MSME Digital Marketing through Public-Private Partnerships with Fuzzy AHP - Bahukeling, Trukan Sri; Suroso, Arif Imam; Buono, Agus; Nurhayati, Popong (Pandawan, 2026)
Public Private Partnership (PPP) is a contractual arrangement between government and private institutions to share resources, tools, and expertise for delivering public services. In Indonesia, PPPs have been widely applied in infrastructure sectors, but little attention has been given to their role in supporting micro, small, and medium enterprises (MSMEs) in adopting digital marketing. This study aims to build a PPP institutional scenario for implementing digital marketing in MSMEs and to formulate a priority strategy for strengthening PPP-based digital marketing policy. A mixed-method approach was employed, combining scenario planning with the Fuzzy Analytical Hierarchy Process (FAHP). Data were collected from 17 experts through in-depth interviews and analyzed using scenario modeling and fuzzy weighting techniques. The findings indicate that developing institutional guidelines, establishing a task force, fostering commitment, and creating PPP patterns are key strategies to enhance MSMEs’ digital adoption. The results highlight the importance of government investment in digital infrastructure, training programs, and supportive regulations. This research provides practical contributions for policymakers in strengthening PPP-based digital ecosystems and academic contributions by advancing scenario-based decision-making for sustainable MSME development.